Attachment Styles and their Demographic Association Among Adult Children of Alcoholic Fathers in Pakistan - Suneel, Ivan; Suneel, Elizabeth Schwaiger; Anthoney, Sarah (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To study the relationship between demographics and attachment styles among adult children of alcoholic fathers. Study Design: Cross-sectional study. Place and Duration of Study: Private Rehabilitation Centers, Lahore Pakistan, from Jan to Apr 2020. Methodology: A sample of almost equal participation of both genders (202 males and 198 females) were included in the study. Two measuring tools were used, a Demographic questionnaire and the Adult Attachment questionnaire. Results: Chi-square test indicated that attachment style was significantly associated with age [p < 0.001], education [p < 0.001], and birth order [p < 0.001], However, gender [p =0.374] and number of siblings [p=0.876] were not significantly associated. Conclusion: There is a relationship between attachment styles and associated demographics of adult children of alcoholic fathers. Based on these findings, the alcoholics and their families could be educated, an intervention plan could be developed, and literature could educate the masses about alcoholism and its impact on children.